2019
DOI: 10.1136/gutjnl-2018-317163
|View full text |Cite|
|
Sign up to set email alerts
|

Localisation of PGK1 determines metabolic phenotype to balance metastasis and proliferation in patients with SMAD4-negative pancreatic cancer

Abstract: ObjectivePancreatic ductal adenocarcinoma (PDAC) is the most aggressive type of GI tumour, and it possesses deregulated cellular energetics. Although recent advances in PDAC biology have led to the discovery of recurrent genetic mutations in Kras, TP53 and SMAD4, which are related to this disease, clinical application of the molecular phenotype of PDAC remains challenging.DesignWe combined molecular imaging technology (positron emission tomography/CT) and immunohistochemistry to evaluate the correlation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 36 publications
1
90
0
Order By: Relevance
“…The AAV packaging was conducted as previously described 33 . Briefly, recombinant AAV (rAAV) vectors were generated by the transient transfection of 293T cells using three AAV plasmids (pAAV8-rep/cap-Y-F mutant, pAAV2-NLS-CasRx-NLS-HA-gRNA/pAAV2-GFP, and pHelper).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AAV packaging was conducted as previously described 33 . Briefly, recombinant AAV (rAAV) vectors were generated by the transient transfection of 293T cells using three AAV plasmids (pAAV8-rep/cap-Y-F mutant, pAAV2-NLS-CasRx-NLS-HA-gRNA/pAAV2-GFP, and pHelper).…”
Section: Methodsmentioning
confidence: 99%
“…PDAC PDX mouse models were established by using freshly isolated pancreatectomy samples as previously described 33 . Briefly, every PDAC sample was isolated in two parts.…”
Section: Methodsmentioning
confidence: 99%
“…DSBs are repaired by BRCA through the gene conversion (GC) pathway in normal cells. However, in BRCA-loss cancer cells, DSBs cannot be repaired and will lead to fatal genomic instability metastatic patterns of PDAC cells and providing guidance for precise therapy [130].…”
Section: Roles Of Smad4 and Related Molecules In Pdac Subtypingmentioning
confidence: 99%
“…SMAD4 can also function as a negative regulatory element in the glucose transport system, targeted by specific miRNAs, such as miR-29a and miR-23a [45]. Liang et al found loss of SMAD4 can enhance glycolysis and aggressive tumor behavior by upregulating phosphoglycerate kinase 1 (PGK1) in PDAC [19]. The relationship between SMAD4 and glutamine metabolism in tumors remains to be further studied.…”
Section: Smad4mentioning
confidence: 99%
“…All clinical trials failed so far either due to its negative safety profiles or the slight effect in clinical trials which is significantly attenuated compared with the effects in preclinical trials [15][16][17]. While on the other hand, more and more research indicated that a series of tumor suppressor genes may provide new ideas in effective pancreatic cancer treatments [18][19][20][21]. Therefore, in this paper, we reviewed recent research about metabolic reprogramming by tumor suppressor genes in pancreatic cancer, and hope to identify novel molecular targets for the development of chemotherapeutic approaches in PDAC (pancreatic ductal adenocarcinoma).…”
Section: Introductionmentioning
confidence: 99%